2000
DOI: 10.1002/1096-9098(200005)74:1<75::aid-jso16>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Integrated treatment in locally advanced carcinoma of the oropharynx

Abstract: The results suggest that surgery followed by radiotherapy seems to be the best treatment in the case of locally advanced oropharyngeal tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…In a review of recent reports, five-year survival rates in oropharyngeal cancer ranged from 45 to 70% for surgery followed by RT (2-5), whereas for CCRT, the majority of studies conducted in patients with advanced stage disease found three-year survival rates in the range 37 to 51% (6-8). Although patients in the CCRT studies appeared to have higher stage disease than in the surgery followed by RT studies, treatment outcomes of CCRT are far from satisfactory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a review of recent reports, five-year survival rates in oropharyngeal cancer ranged from 45 to 70% for surgery followed by RT (2-5), whereas for CCRT, the majority of studies conducted in patients with advanced stage disease found three-year survival rates in the range 37 to 51% (6-8). Although patients in the CCRT studies appeared to have higher stage disease than in the surgery followed by RT studies, treatment outcomes of CCRT are far from satisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, organ preservation was possible in only 24% of patients (6 out of 25), which shows that the oropharynx is a less satisfactory site for organ preservation than the larynx, which was preserved in 71.4% of patients (10 out of 14). Lanza et al (8) compared the results of surgery with RT and neoadjuvant chemotherapy followed by RT in 115 T3-4 patients. The three-years OSRs of the respective treatment groups were 82 and 49%, showing that surgery-based therapy appeared to be the better treatment option.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with oropharyngeal squamous cell carcinoma (OPSCC) may be treated in a curative intent with surgery as a single modality in early stage disease, [1][2][3][4] or with surgery followed by (chemo)radiation or primary (chemo)radiation (RT) in more advanced stages. 2,[5][6][7] Management decisions are based on the likelihood for cure and the respective morbidity of the therapeutic options. Patients with early stage disease may be successfully treated with surgery alone in order to avoid radiation associated xerostomia.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Treatment options include primary radio(chemo)therapy, surgery alone, and surgery followed by radio(chemo)therapy. [6][7][8][9][10] In recent years, there has been a shift toward nonsurgical primary management of advanced HNSCC of the oropharynx. 5,11,12 Regardless of the treatment modality, patients with HNSCC of the oropharynx carry a high risk of recurrence after initial therapy.…”
mentioning
confidence: 99%